2023
DOI: 10.3390/app132212356
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Vibrations of Mass(es) Moving Uniformly on a Two-Layer Track Model: Parameters Leading to Irregular Cases and Associated Implications for Railway Design

Zuzana Dimitrovová

Abstract: Ballasted railway tracks can be modeled using reduced/simplified models composed of several layers of discrete components. This paper deals with the two-layer model, which is very popular due to its computational efficiency. In order to provide some recommendations for track design, it is necessary to identify which set of parameters leads to some irregular/unexpected behavior. In this paper, irregularities are investigated at three levels, namely, (i) the critical velocity of a moving constant force, (ii) the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…It is demonstrated that there are several situations with rather unpredictable behavior, especially at low damping levels, as already shown for simpler, one-layer [34] and two-layer models [35,51]. In the semi-analytical approach, the so-called instability lines are traced, indicating the moving mass as a function of velocity in a limiting situation where one of the induced frequencies is real-valued.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…It is demonstrated that there are several situations with rather unpredictable behavior, especially at low damping levels, as already shown for simpler, one-layer [34] and two-layer models [35,51]. In the semi-analytical approach, the so-called instability lines are traced, indicating the moving mass as a function of velocity in a limiting situation where one of the induced frequencies is real-valued.…”
Section: Introductionmentioning
confidence: 64%
“…As already mentioned in the Introduction, the three-viscoelastic-layer railway track model is widely used for its simplicity, numerical efficiency, and ability to effectively estimate the real behavior, as demonstrated in [71,72]. Its description was already given in previous works on layered models [51,52], but it is repeated here for completeness. In this model, the rail is modeled by a beam that is supported by linear spring-damper elements standing for rail pads, which are connected to point masses representing sleepers' masses, which are, in turn, supported by linear spring-damper elements modeling the ballast, including its shear resistance.…”
Section: Mechanical Model and Governing Equationsmentioning
confidence: 99%
See 3 more Smart Citations